A formação intelectual de jovens do ensino médio: caminhos e possibilidades para o pensar autônomo - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2016)
This research investigates the intellectual training of public high school young students. And tries to answer the following question: How does high school students of the Pará State Eas tern Region Federal University Linguistic Study Group, in Santarém, develop themselves in telectually in contact with the University environment, rich in different academic and intellec tual experiences? This study was based upon Theodor Adorno Critical Theory and other rese archers. The literature review testified that there are few research works regarding the intelec tual training of high school young students within systematic formative experiences such as the scientific study iniciation provided by the GELOPA Linguistic Study Group. The research opted for a longitudinal monitoring between August 2014 to August 2015 which corresponds to the duration of the PIBIC-EM Scientific Iniciation Scholarship. The research was develo ped through a Case Study and the data was collected via the application of questionaires and semi structured interviews to the students. The content of the questionaires and the interviews pointed out that there is a building of knowledge inherent to the scientific research and also that they reflected in a new organization of thoughts and in the dvelopment of autonomous thinking before the reified concepts common in school environment. A qualitative approach was conducted for the analysis of the collected data, in the first part of the study, the model of ethnographic profile narratives were used base upon the works of Bernard Lahire (2004), then, the analysis was done by taking into account the categories that emerged during data processing. This research investigated six 2nd graders of a State public high school. The re sults demonstrated that the young students had a relevant intellectual gain during the period of time that they were in contact with different formative experiences in the GELOPA Linguistic Study Group, since they had an increase in scientific knowledge, resignfication of already known concepts about their mother language, descoveries of cognitive potentials, deve lopment of self evaluation, confidence building, and group work skills.
Keywords: Educação; Ensino médio; Formação intelectual; Teoria crítica; CNPQ::EDUCAÇÃO::EDUCAÇÃO PERMANENTE::TEORIA CRÍTICA; PRÁTICAS EDUCATIVAS, LINGUAGENS E TECNOLOGIAS.; EDUCAÇÃO. ENSINO MÉDIO.TEORIA CRÍTICA